Sebuah Usulan Desain Produk: Sandal Kesehatan dengan Konsep Desain Personalisasi - Devanny Gumulya; Winston Jauri (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2016)
Footwear is essential human being to do many activities, such as working and relax activities. Footwear protects ourfoot from all kinds of objects that can be dangerous. Recently, there is healthy lifestyle trend, we can see from the emergence of many health products. One such product is the healthy sandals. However, these healthy sandals have problems such as they don't provide much health effects, but only give prejudice so that consumers want to buy it. In terms of product styling, they are very bad, so the target consumer is very specific, they don't have mass market interest. But there is a  design opportunity here.The solution proposed is to design a sandal with personalized insole, so customers can choose the most comfort insole to solve theirfoot problems such asflatfeet, pain in the metatarsal, heel pain, calluses, and a few other problems. Hopefolly with this concept finally health sandal can give healthy effect notjust a prejudice.  This project  is supported by a sandal manufacturer, PT. TBS Design Center.Keywords  : Ergonomi,  Consumer  Goods, Health and Lifestyle